The ludic in the development of musical creative potentialities in early childhood (2020)
This paper presents a vision of the creative musical development in the early childhood (from two to five years old ) departing from the sound exploration to the construction of a children's own musical making, having the playful activity as a structural basis for learning. We understand that the development of creative potential using the sound and the noise as a material of exploration allows the expansion of ideas and musical concepts, providing the formation of active, perceptive, sensitive and insightful subjects for a differentiated and open relationship with the world around the children. Based on the proposals of François Delalande and their interfaces with theorists such as Gilles Deleuze and Johan Huizinga, we propose an approach aimed at an age group which, although foreseen in Delalande's theoretical proposals, this particular age group is not sufficiently addressed in teaching. At the end, we present an experience report conducted in regular school with kindergarten students.